Bank supervision Russian style: Evidence of conflicts between micor- and macroprudential concerns - Sophie Claeys; Koen Schoors (Sveriges Riksbank, 2007)
Supervisors sometimes have to manage both the micro- and macro- prudential dimensions of bank stability. These may either conflict or complement each other. We analyze prudential supervision by the Central Bank of Russia (CBR). We find evidence of micro-prudential concerns, measured as the rule-based enforcement of bank standards. Macro-prudential concerns are also documented: Banks in concentrated bank markets, large banks, money center banks and large deposit banks are less likely to face license withdrawal. Further, the CBR is reluctant to withdraw licenses when there are 'too many banks to fail'. Finally, macro-prudential concerns induce regulatory forbearance, revealing conflicts with micro-prudential objectives.
Keywords: G2; N2; E5; 330; prudential supervision; bank stability; systemic stability; Bankenaufsicht; Finanzsystem; Bankenliquidität; Russland